Багатокритеріальні задачі прийняття рішень в нечітких умовах і методи їх розв’язання - Zaychenko, Ju. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Problems of decision-making with (using) multiple criteria under uncertainty, when parameters of goal functions and constants are fuzzy sets, are considered. For multi-criteria linear programming problem suggested is the method which enables to find compromise solution for a pair of pessimist and optimist tasks. For general multi-criteria non-linear programming problem with fuzzy parameters the method based on finding of the Pareto-optimal solution of α-level is suggested.